2012
DOI: 10.1002/eji.201142035
|View full text |Cite
|
Sign up to set email alerts
|

Expression of IL‐1Rrp2 by human myelomonocytic cells is unique to DCs and facilitates DC maturation by IL‐1F8 and IL‐1F9

Abstract: We report for the first time that expression of the novel IL-1 cytokine receptor IL-1Rrp2 (IL-1R6) is unique to DCs within the human myelomonocytic lineage. IL-1Rrp2 was expressed by monocyte-derived dendritic cells (MDDCs) which was dose-dependently increased by IL-4 and correlated with increased numbers of differentiated MDDCs. Human plasmacytoid DCs also express IL-1Rrp2 but the receptor is not expressed by either myeloid DC type 1 (mDC1) or mDC2 cells. We also show that IL-1F8 or IL-1F9 cytokines, which si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
83
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 32 publications
3
83
1
1
Order By: Relevance
“…We then studied whether, or not, IL-36 β altered expression of IL-36R in CD4+ lymphocytes and found that IL-36R expression plateaued when the cells were incubated with 100-200 ng/ml IL-36β. Human IL-36α-γ have been shown before to be effective at relatively low doses, when compared to murine homologues [12][13]. The current study is, therefore, consistent with the latter since culture of CD4+ cells with IL-1β at 500 ng/ml decreased IL-36R expression, when compared to expression at 100-200 ng/ml, which also indicates a negative feedback loop shown in a previous paper [12].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We then studied whether, or not, IL-36 β altered expression of IL-36R in CD4+ lymphocytes and found that IL-36R expression plateaued when the cells were incubated with 100-200 ng/ml IL-36β. Human IL-36α-γ have been shown before to be effective at relatively low doses, when compared to murine homologues [12][13]. The current study is, therefore, consistent with the latter since culture of CD4+ cells with IL-1β at 500 ng/ml decreased IL-36R expression, when compared to expression at 100-200 ng/ml, which also indicates a negative feedback loop shown in a previous paper [12].…”
Section: Discussionsupporting
confidence: 91%
“…Lamina propria cells were isolated from mucosal samples using a previously described technique [9]. table 1and as previously reported [12][13] and PCR product obtained was also shown to be of correct size as that previously reported [12].…”
Section: Isolation Of Human Ileal Lamina Propria Cellsmentioning
confidence: 66%
See 2 more Smart Citations
“…IL-36 cytokines are new members of the IL-1 family that comprise three agonists, IL-36a, IL-36b, and IL-36g, that bind to the IL-36R and recruit the coreceptor IL-1R accessory protein, activating intracellular signals similar to those induced by other members of the IL-1 family. IL-36a, IL-36b, and IL-36g can stimulate the production of different cytokines by both human and mouse dendritic cells (DCs) (21,22). IL-36b can induce proliferation and IL-2 secretion in naive mouse T cells (Th0), and synergizes with IL-12 to stimulate Th1 responses (23).…”
mentioning
confidence: 99%